Panduan Konseling Kelompok Teknik Self-Instruction untuk Meningkatkan Kepercayaan Diri dan Sikap Asertif Santri Korban Bullying - Athifah, Nurul; Muslihati, Muslihati; Rahman, Diniy Hidayatur (citeus, 2025)
This development study aims to produce a collective self-education guide for counselors that is both interesting and easy to understand. Group counseling guidelines are used according to the evolution of Borg and Gall. The steps involved in developmental research up to the seventh level are as per requirements and are in the product review phase after materials expert testing, media expert testing, and product user candidate (consultant) testing at Izzat Batu Secondary School. school. Research and development results show that a group counseling guide to self-educational techniques scores from guidance and counseling experts with an agreement model among raters showing very high standards of 1 from media experts as 1 and from potential users (advisers) as 1. Based on the assessment of experts that the counseling guide for self instruction is very feasible to use.